Covalently Assembled Dipeptide Nanoparticles with Adjustable Fluorescence Emission for Multicolor Bioimaging. (19th November 2018) - Li, Shukun; Liu, Yamei; Xing, Ruirui; Yan, Xuehai
Abstract: Peptide self‐assembly, inspired by the naturally occurring fabrication principle, remains the most attractive in constructing fluorescent nanoagents towards bioimaging. However, the noncovalent interactions that drive peptide self‐assembly are usually susceptible to the complex physiological environment; thus leading to disassembly and dysfunction of fluorescent nanoagents. Herein, a covalently crosslinked assembly strategy for fabrication of stable peptide‐based nanoparticles with adjustable emission is introduced. In the process of cationic diphenylalanine peptide (H‐Phe‐Phe‐NH2 ⋅ HCl) self‐assembly, glutaraldehyde is used as a crosslinker and the resulting product of the Schiff base reaction can be fluorescent. More importantly, the emission wavelength can be readily tuned by controlling the covalent reaction time. It has been demonstrated that the nanoparticles are stable, even after intracellular uptake, and can be used for sustainable multicolor fluorescent imaging. The strategy with integrating peptide self‐assembly and covalent crosslinking could be promising for the design and engineering of functional fluorescent nanoparticles with robust physiological stability and adjustable emission towards improved bioimaging applications. Abstract : Illuminating cells : The self‐assembly of cationic dipeptides (CDPs), in combination with glutaraldehyde (GA) crosslinking, results in the formation of robust nanoparticles (NPs) with adjustable fluorescence emission. These NPs can be used for multicolor imaging of cells for improved bioimaging efficacy.